Covalent adaptable microstructures via combining two‐photon laser printing and alkoxyamine chemistry: toward living 3D microstructures [data] - Spiegel, Christoph A.; Jia, Yixuan; Welle, Alexander; Heißler, Stefan; Sedghamiz, Elaheh; Liu, Modan; Wenzel, Wolfgang; Hackner, Maximilian; Spatz, Joachim P.; Tsotsalas, Manuel; Blasco, Eva (Universität, 2024)
Manufacturing programmable materials, whose mechanical properties can be adapted on demand, is highly desired for their application in areas ranging from robotics, to biomedicine, or microfluidics. Herein, the inclusion of dynamic and living bonds, such as alkoxyamines, in a printable formulation suitable for two-photon 3D laser printing is exploited. On one hand, taking advantage of the dynamic covalent character of alkoxyamines, the nitroxide exchange reaction is investigated. As a consequence, a reduction of the Young´s Modulus by 50%, is measured by nanoindentation. On the other hand, due to its “living” characteristic, the chain extension becomes possible via nitroxide mediated polymerization. In particular, living nitroxide mediated polymerization of styrene results not only in a dramatic increase of the volume (≈8 times) of the 3D printed microstructure but also an increase of the Young's Modulus by two orders of magnitude (from 14 MPa to 2.7 GPa), while maintaining the shape including fine structural details. Thus, the approach introduces a new dimension by enabling to create microstructures with dynamically tunable size and mechanical properties.
Gefördert durch: Deutsche Forschungsgemeinschaft: BL-1604/2-1, Deutsche Forschungsgemeinschaft: “3D Matter Made to Order” (EXC-2082/1-390761711), Carl Zeiss Foundation: “Carl-Zeiss-Foundation-FocusHEiKA”, Helmholtz program: “Materials Systems Engineering” (MSE), Max Planck Society
Gesehen am 13.03.2025
Keywords: Forschungsdaten; Datenbank